2023
DOI: 10.3390/ijms241813715
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lenvatinib Combined with Transcatheter Intra-Arterial Therapies for Patients with Advanced-Stage of Hepatocellular Carcinoma: A Propensity Score Matching

Shigeo Shimose,
Hideki Iwamoto,
Takashi Niizeki
et al.

Abstract: This study aimed to evaluate the effect of lenvatinib (LEN) combined with transcatheter intra-arterial therapy (TIT) for advanced-stage hepatocellular carcinoma (HCC) after propensity score matching (PSM). This retrospective study enrolled 115 patients with advanced-stage HCC who received LEN treatment. The patients were categorized into the LEN combined with TIT group (n = 30) or the LEN monotherapy group (n = 85). After PSM, 38 patients (LEN + TIT group, n = 19; LEN monotherapy group, n = 19) were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…29 Propensity scores for all the patients were estimated by a logistic regression model using the baseline characteristics of age and smoking as covariates as previously described. [31][32][33] Data were analyzed using JMP Pro15 (SAS Institute Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…29 Propensity scores for all the patients were estimated by a logistic regression model using the baseline characteristics of age and smoking as covariates as previously described. [31][32][33] Data were analyzed using JMP Pro15 (SAS Institute Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many studies suggest the introduction of a novel approach based on "converse therapeutic hierarchy" [6], in which the advanced treatment modalities may be better integrated to achieve patient-tailored management. In this context, we included a retrospective study enrolling 115 HCC patients at advanced stage who received lenvatinib (LEN) combined with transcatheter intra-arterial therapy (TIT) after propensity score matching observed that this combination therapy may improve prognosis with respect to lenvatinib monotherapy in advanced HCC patients, particularly those <75 years of age and with modified albumin bilirubin (m-ALBI) grade 1 [7].…”
mentioning
confidence: 99%